2013
DOI: 10.1021/es304425r
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Medium-Chain Chlorinated Paraffins in Air and Soil of Subtropical Terrestrial Environment in the Pearl River Delta, South China: Distribution, Composition, Atmospheric Deposition Fluxes, and Environmental Fate

Abstract: Research on the environmental fate of shortand medium-chain chlorinated paraffins (SCCPs and MCCPs) in highly industrialized subtropical areas is still scarce. Air, soil, and atmospheric deposition process in the Pearl River Delta of South China were investigated, and the average SCCP and MCCP concentrations were 5.2 μg/sampler (17.69 ng/m 3 ) and 4.1 μg/sampler for passive air samples, 18.3 and 59.3 ng/g for soil samples, and 5.0 and 5.3 μg/(m 2 d) for deposition samples, respectively. Influenced by primary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
84
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 40 publications
16
84
3
Order By: Relevance
“…This observation is consistent with long-range atmospheric/oceanic transport of CPs to this region. 37,45 The pattern of dolphins had higher proportions of the less volatile CP congeners, implying that contamination of this region is higher, probably from primary discharge from the PRD.…”
Section: ■ Materials and Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…This observation is consistent with long-range atmospheric/oceanic transport of CPs to this region. 37,45 The pattern of dolphins had higher proportions of the less volatile CP congeners, implying that contamination of this region is higher, probably from primary discharge from the PRD.…”
Section: ■ Materials and Methodsmentioning
confidence: 98%
“…Dolphins have greater proportions of C 12−13 within SCCPs and more C 14 within MCCPs compared to porpoises. This implies that a fractionation of congeners with different physicochemical properties during the complex environmental processes, including local inputs, atmospheric transport, oceanic transport, prey preference, and trophic transfer or a combination of all of these, may be attributed to differences in the CP homologue patterns.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Many studies demonstrate that the Pearl River Delta region have become a hotspot area for persistent halogenated compound contamination due to rapid industrialization and urbanization, and intensive e-waste recycling activities (Fu et al, 2003;Mai et al, 2005aMai et al, , 2005b. High levels of ∑SCCPs were observed in various environmental matrices such as sediment (320-6600 ng·g − 1 dry weight, dw), soil (18 ng·g − 1 dw, average), and air samples (18 ng·m − 3 , average) obtained from this region (Chen et al, 2011;Wang et al, 2013). Luo et al (2015) reported that ∑SCCP concentrations in terrestrial bird species inhabiting an e-waste recycling site in the Pearl River Delta, South China ranged from 620 to 17,000 ng·g −1 lipid weight (lw).…”
Section: Introductionmentioning
confidence: 99%
“…Active air samplers and passive air samplers are frequently used to investigate the atmospheric levels and distribution of SVOCs (Hayward et al, 2010), but these need to be deployed at each site and revisited during collection. These sampling methods have also been previously used for evaluating the levels of SCCPs in the atmosphere (Wang et al, , 2013Li et al, 2012). On the other hand, vegetation can also accumulate considerable amounts of SVOCs from the atmosphere by gas-phase partitioning process and/or deposition of particle bound residues.…”
Section: Introductionmentioning
confidence: 99%